KEY FACTORS INFLUENCING THE EFFECTIVENESS OF GAMIFICATION IN ACCOUNTING EDUCATION - Ros Amalina Zakaria; Nik Zam Nik Wan; Azilawati Abdullah @ Abd Aziz; Siti Nor Adawiah Hussin; Nor Asmawani Che Hassan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The integration of gamification in education has gained substantial attention in recent years, particularly in fields like accounting, where traditional teaching methods can sometimes fail to engage students effectively. This paper explores the factors that contribute to the effectiveness of gamification in accounting education. The problem lies in the challenge of engaging students in a subject that is often perceived as dry and difficult. Accounting educators face the ongoing task of creating dynamic, interactive learning experiences that enhance both understanding and motivation. This study aims to identify key factors that influence the success of gamification in accounting courses. A literature review methodology will be employed to gather and synthesize research findings from various sources, including academic journals, books, and case studies. The finding reveals gamification effectiveness is contributed by thoughtful design of gamification strategy which align with learning objectives, technological infrastructure, student motivation, educator involvement and the use of timely feedback mechanism. The benefits of this paper are twofold: first, it will provide educators with a clearer understanding of how gamification can enhance student engagement and retention in accounting courses; second, it will contribute to the broader discourse on innovative teaching methods in higher education, specifically within accounting. The findings of this study are expected to guide future pedagogical strategies and inform curriculum development in accounting programs globally.